(untitled) (Journal of human and social sciences, 2023)
This study aims to highlight unemployment in the Arab world as one of the major economic and social challenges that threaten community stability and hinder development efforts. It explores the causes and different types of unemployment, outlining its negative impacts on living conditions, health, education, and social cohesion. The study also discusses coping strategies, including economic and educational reforms, labor market support, and investment promotion, in order to reduce unemployment rates and strengthen social development.